PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA BAAMBOOZLE TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD NEGERI 060971 MEDAN TUNTUNGAN - Br Sitepu, Risna Wati; Patri Janson Silaban; Heka Maya Sari Sembiring; Regina Sipayung; Juliana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Problem-Based Learning (PBL) model using Baamboozle media on the science learning outcomes of grade IV students at SD Negeri 060971 Medan Tuntungan in the 2025/2026 ACADEMIC YEAR. This study uses a quantitative method with a One Group Pretest-Posttest Design involving 23 students as samples. Data collection techniques used tests and questionnaires, while data analysis was carried out through normality tests, Product Moment correlations, coefficients of determination, and hypothesis testing (paired sample t-tests). The results showed that the average student pretest score was 56.39 and the average posttest score was 79.69. The average questionnaire score for the Problem Based Learning (PBL) learning model assisted by Baamboozle media obtained by students was 103.78. The results of the correlation test obtained a value of 0.972 with a very strong category and a coefficient of determination of 94.48%. The hypothesis test showed a t_count value of 11.772 > t_table of 2.074 with a significance value of 0.000 <0.05. Thus, it can be concluded that the Problem-Based Learning (PBL) model using Baamboozle media has a positive and significant effect on the science learning outcomes of fourth-grade students at SD Negeri 060971 Medan Tuntungan in the 2025/2026 academic year.